Все позволенно. "Братья Карамазовы" в современном театре - Lappo, Irina (Colloquia Litteraria, 2019)
Irina Lappo, “Everything is Permitted. «The Karamozov Brothers» in contemporary Theatrical performances” The paper, after a brief analysis of the basic motifs and structural features of Dostoyevsky’s novels, opens with the description of the historical performance of The Karamazov Brothers from 1910 presented in Moscow Artistic Theatre (MCHAT) and directed by Niemirovitsch-Dancenko. The main theme of this paper are three key performance of Dostoyevsky’s final novel: by Janusz Opryski (2010), Sylwa Kricikene (2011) and Lev Erenburg (2016).